Intelligent systems : architecture, design, and control - Meystel, A. (Alex); Albus, Jim. (New Delhi ; Chichester : Wiley, 2015)
This comprehensive treatment of the field of intelligent systems is written by two of the foremost authorities in the field. The authors clearly examine the theoretical and practical aspects of these systems. The book focuses on the NIST-RCS (Real-time Control System) model that has been used recently in the Mars Rover.
Keywords: Intelligent control systems